Modelagem computacional de efeitos dinâmicos de dissipação de energia em transientes hidráulicos - Ferreira, Fábio Eduardo Franco Rodrigues (2011)
Elevated pressures caused by sudden and unexpected shutdown of pumps are usually responsible for structural damage in water pipes. An effective control of these losses requires an adequate designing of system or devices whose purpose is relieving the water hammer effects. This adjustment depends on the proposed formulations for the equations of continuity and momentum of the water hammer phenomenon. In this sense, the consideration of more accurate models has been useful for the designing of hydraulic systems. Many analyses have been made for transients caused by opening or closing of valves, but little progress has been made in the analysis of transients caused by sudden and unexpected shutdown of pumps. Thus, the main objective of this work is to implement a computational program that takes into consideration formulations of variable friction term and mechanical behavior of plastic pipes in transients caused by sudden pump shutdown in water pipe. Satisfactory results were obtained for a hydraulic model that considers the viscoelastic behavior of the pipes. The variable friction models showed no satisfactory results for this type of transient event.